The reception and the party after: how vascular endothelial growth factor receptor 2 explores cytoplasmic space (Swiss Medical Weekly, 2011)
Vascular endothelial growth factors (VEGFs) regulate blood and lymph vessel formation through activation of the type V receptor tyrosine kinases VEGFR-1, -2 and -3. In addition, VEGFs interact with co-receptors such as neuropilins, integrins, semaphorins or heparansulfate glycosaminoglycans. Ligand binding dimerises the receptors and activates their intracellular tyrosine kinase domains, resulting in phosphorylation of tyrosine residues acting as docking sites for intracellular signalling molecules. Ligand-induced receptor is internalised and then transported through early, late, and recycling endosomes, and finally degraded by proteasomal or lysosomal pathways. Biological output by VEGF is mediated through distinct receptor/co-receptor complexes and generates signals in all cellular compartments triggering cellular responses such as cell migration, cell proliferation, vessel formation and maturation, as well as changes in vessel fenestration, constriction and permeability. Here we review recent experiments showing how VEGFR-2 is transported through intracellular vesicular compartments specified by Rab family GTPases, and discuss how different VEGF-A isoforms specify intracellular receptor trafficking. We also discuss how the biological consequences of aberrant receptor trafficking bear on the development of vascular disease.